On IT enabling of business process reengineering in organizations - Sungau, Joseph Joseph; Msanjila, Samwel (Trans Tech Publications Ltd, 2024)
Article published by Trans Tech Publications Ltd in the Journal of Advanced Materials research (Volumes 403-408)